First-Principles Study of Vacancy and Impurities Defects in Graphene - Neupane, Hari Krishna; Adhikari, Narayan Prasad (Amrit Research Journal, 2021)
In this work, we have studied the electronic and magnetic properties of 1C atom vacancy defects in graphene (1Cv-d-G), 1N atom impurity defects in graphene (1NI-d-G) and 1O atom impurity defects in graphene (1OI-d-G) materials through first principles calculations based on spin-polarized density functional theory (DFT) method, using computational tool Quantum ESPRESSO (QE) code. From band structure and density of states (DOS) calculations, we found that supercell structure of monolayer graphene is a zero bandgap material. But, electronic bands of 1Cv-d-G, 1NI-d-G and 1OI-d-G materials split around the Fermi energy level and DOS of up & down spins states appear in the Fermi energy level. Thus, 1Cv-d-G, 1NI-d-G and 1OI-d-G materials have metallic properties. We have studied the magnetic properties of pure and defected materials by analyzing density of states (DOS) and partial density of states (PDOS) calculations. We found that graphene and 1OI-d-G materials have non-magnetic properties. On the other hand, 1C vacancy atom and 1N impurity atom induced magnetization in 1Cv-d-G & 1NI-d-G materials by the rebonding of dangling bonds and acquiring significant magnetic moments of values -0.75μB/cell & 0.05μB/cell respectively through remaining unsaturated dangling bond. Therefore, non-magnetic graphene changes to magnetic 1Cv-d-G and 1NI-d-G materials due to 1C atom vacancy defects and 1N atom impurity defects. The 2p orbital of carbon atoms has main contribution of magnetic moment in these defected structures.